Synthesis and antibacterial Activity of 1-H-3-(2’-Hydroxy-4’-ethyoxy-5’-bromo phen-1’yl)-5-substituted Phenyl-2-pyrazolines and Their Related Compounds - M. Barot, Vijay (Asian Journal of Chemistry, 2010)
In the present note the author describes the synthesis and antibacterial activity of 1-H-3-(2´-Hydroxy-4´-ethoxy-5´-bromo phen-1´-yl)-5-substituted phenyl-2-pyrazolines and their related compounds.